Shifts in growth phenology of Tsuga dumosa in the central Himalayas under climate warming - Samresh Rai; Filipe Campelo; Jiri Dolezal (Agricultural and Forest Meteorology, 2026)

Growth dynamics and climate sensitivities in alpine cushion plants: insights from Silene acaulis in the Swiss Alps - Samresh Rai; Nikola Breme; Veronika Jandova; Vojtech Lanta; Jan Altman; Adam Taylor Ruka; Christian Rixen; Jiri Dolezal (Alpine Botany, 2025)
Understanding alpine plants’ growth dynamics and responses to warming is essential for predicting climate change impacts on mountain ecosystems. Here, we examine growth determinants in the alpine cushion plant Silene acaulis in the Swiss Alps, exploring ontogeny, elevation, and climate influences. We collected 40 Silene individuals and 159 individuals from 38 co-occurring alpine species across 2200–3130 m elevations in the Swiss Alps, analyzing age and growth histories through annual growth rings. While comparing growth rates, we found that Silene was relatively slow-growing. However, Silene exhibited a dual growth strategy, initially rapid and then slowing after ~ 20 years, challenging perceptions of its longevity. Similar ontogenetic trends were observed in other alpine species, albeit with variations based on species and elevation. The consistent unimodal growth-elevation pattern in Silene and other alpine plants, peaking at ~ 2400 m, underscores shared environmental constraints on alpine plant growth. Additionally, cross-dating growth ring series and correlating with daily climate data enabled the precise assessment of warming impacts on growth. Silene ’s growth is influenced by year-to-year climate variability, with warming-induced moisture stress and overheating during spring and summer adversely affecting its growth. Despite being low-statured, Silene is not completely decoupled from atmospheric influences. The heat-trapping function of Silene , effective in mature and well-formed cushions, makes it susceptible to adverse effects as temperatures rise. This sensitivity raises concerns about the potential dieback of Silene cushions, as witnessed during recent heatwaves, and emphasizes the broader ecological implications for alpine ecosystems, given Silene ’s role as a crucial nurse plant.

Climate drivers of Pinus ponderosa tree development on volcanic tephra deposits in the Southwestern USA: Insights from radial increment and wood density variations - Julieta Gabriela Arco Molina; Jan Altman; Samresh Rai; Kirill Korznikov; Vit Pejcha; Miroslav Dvorsky; Jiri Doležal (Dendrochronologia, 2024)

Elevational variations in climate warming impacts on West Himalayan fir growth - Kristina Sohar; Jan Altman; Martin Kopecký; Vít Pejcha; Samresh Rai; Pavel Fibich; Jiří Doležal (Climate Dynamics, 2024)

Global warming alters Himalayan hemlock’s climate sensitivity and growth dynamics - Samresh Rai; Jan Altman; Martin Kopecký; Vít Pejcha; Miroslav Svoboda; Jiří Doležal (Climate Dynamics, 2024)

Contrasting impacts of climate warming on Himalayan Hemlock growth: Seasonal and elevational variations - Samresh Rai; Jan Altman; Martin Kopecký; Kristina Sohar; Pavel Fibich; Vít Pejcha; Jiří Doležal (Dendrochronologia, 2023)